Penyuluhan Persiapan Menarche Pada Remaja Putri di Pondok Tahfidz Qur’an Hisbah Al Fatih Sintang - Dian Ika Pratiwi; Arum Seftiani Lestari; Atri Rudtitasari; Tri Endah Suryani (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
Adolescence is a period of transition from child to teenager starting with physical, psychological, emotional, hormonal, and mental growth and development related to sexual maturity. Sexual maturity is indicated by the presence of menarche. Survey Demography Kesehatan Indonesia (SDKI) (2017), states that one in five Indonesian children has not received knowledge about menstruation before getting menarche. Many teenagers are not ready to get menarche, some are sad, confused, crying, and afraid. The purpose of the activity is to increase the knowledge of teenage girls about preparing for menarche. The method of activity is health education for menarche preparation including surveys, determining the implementation schedule and data collection, pre-test, and health education activities with health education media, namely videos and leaflets. The activity was held on July 9, 2022, at Pondok Tahfidz Qur'an Hisbah Al Fatih Sintang which was attended by 16 teenage girls between the ages of 10-14 years. Post-test and evaluation of questionnaire data processing with Paired Sample Test. The results of data analysis showed changes in the knowledge of teenage girls pre-test and post-test Sig. (2-tailed) of 0.000 < 0.05. The conclusion is that there is a difference in the increase in knowledge before and after giving the health education for menarche preparation for teenage girls at Pondok Tahfidz Qur'an Hisbah Al Fatih Sintang. This health education activity increases the teenage girl's knowledge about menarche preparation so that they are ready, not afraid, and understand about menarche preparation.